2015
DOI: 10.1073/pnas.1501049112
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of diversity, population structure, virulence, and antimicrobial resistance in Klebsiella pneumoniae , an urgent threat to public health

Abstract: Klebsiella pneumoniae is now recognized as an urgent threat to human health because of the emergence of multidrug-resistant strains associated with hospital outbreaks and hypervirulent strains associated with severe community-acquired infections. K. pneumoniae is ubiquitous in the environment and can colonize and infect both plants and animals. However, little is known about the population structure of K. pneumoniae, so it is difficult to recognize or understand the emergence of clinically important clones wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

84
1,123
10
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,041 publications
(1,295 citation statements)
references
References 69 publications
84
1,123
10
19
Order By: Relevance
“…12 Unlike K. variicola, K. quasipneumoniae has been described exclusively in hospital settings. 13 A recent genomic comparative study with a large number of Klebsiella genomes showed that the nif operon was detected in all the genomes of K. variicola, in half of those of K. quasipneumoniae, but only in one strain of K. pneumoniae. 13 Additionally, K. pneumoniae and K. variicola shared some virulence determinants that cause infections in humans.…”
Section: Salud Pública De México / Vol 60 No 1 Enero-febrero De 2018mentioning
confidence: 99%
See 3 more Smart Citations
“…12 Unlike K. variicola, K. quasipneumoniae has been described exclusively in hospital settings. 13 A recent genomic comparative study with a large number of Klebsiella genomes showed that the nif operon was detected in all the genomes of K. variicola, in half of those of K. quasipneumoniae, but only in one strain of K. pneumoniae. 13 Additionally, K. pneumoniae and K. variicola shared some virulence determinants that cause infections in humans.…”
Section: Salud Pública De México / Vol 60 No 1 Enero-febrero De 2018mentioning
confidence: 99%
“…13 A recent genomic comparative study with a large number of Klebsiella genomes showed that the nif operon was detected in all the genomes of K. variicola, in half of those of K. quasipneumoniae, but only in one strain of K. pneumoniae. 13 Additionally, K. pneumoniae and K. variicola shared some virulence determinants that cause infections in humans. 14,15 Some Klebsiella isolates have been misclassified 16,17 and consequently the taxonomic descriptions of their genome sequences in NCBI repositories are inaccurate.…”
Section: Salud Pública De México / Vol 60 No 1 Enero-febrero De 2018mentioning
confidence: 99%
See 2 more Smart Citations
“…The first reported β-lactamases TEM-1/2 and SHV-1, described since 1960 from E. coli and Klebsiella pneumoniae were usually chromosomal. They are the most medically important species, often isolated from severe infections in hospitalized or ambulatory patients [25][26][27][28][29]. Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%